2017
DOI: 10.1097/01.aoa.0000527017.02135.a6
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Severe Maternal Morbidity From Hemorrhage Using a State Perinatal Quality Collaborative

Abstract: (Am J Obstet Gynecol. 2017;216(3):298.e1–298.e11) While obstetric hemorrhage is the most common cause of maternal mortality in the world, it is also the most preventable cause of maternal mortality in the United States. The present study sought to determine whether a tool kit of best practices and implementation strategies for the care of a mother with hemorrhage developed by the California Maternal Quality Care Collective (CMQCC) can reduce severe maternal morbidity (SMM) from obstetric hemorrhage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(70 citation statements)
references
References 0 publications
0
68
1
1
Order By: Relevance
“…Previous research has shown that implementing maternal safety bundles for obstetric hemorrhage can effectively reduce severe maternal morbidity. 31 Broader adoption of such safety bundles and assessment of similar strategies for reducing other obstetric complications and severe newborn morbidities merit further attention. We found two institutional characteristics associated with hospital performance in combined maternal and newborn outcomes-type of ownership and delivery volume.…”
Section: F I G U R Ementioning
confidence: 99%
“…Previous research has shown that implementing maternal safety bundles for obstetric hemorrhage can effectively reduce severe maternal morbidity. 31 Broader adoption of such safety bundles and assessment of similar strategies for reducing other obstetric complications and severe newborn morbidities merit further attention. We found two institutional characteristics associated with hospital performance in combined maternal and newborn outcomes-type of ownership and delivery volume.…”
Section: F I G U R Ementioning
confidence: 99%
“…On the other hand, quantitative blood loss (QBL) is laborious and time consuming but has a lower rate of error. Due to its accuracy, the use of QBL has been encouraged by the California Maternal Quality Care Collaborative (CMQCC) and the Association of Women's Health, Obstetric and Neonatal Nurses (AWHONN) . This point should be considered in future studies.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, neither early umbilical cord clamping nor umbilical cord traction have been shown to have a significant effect on the incidence or volume of postpartum hemorrhage (32). Additionally, in a Cochrane review, two trials examining nipple stimulation or breastfeeding did not demonstrate a difference in postpartum hemorrhage (33,34).…”
Section: What Should Be Considered In the Initial Evaluation And Manamentioning
confidence: 98%